2005
DOI: 10.1086/502599
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin for Controlling Methicillin-ResistantStaphylococcus Aureus: Lessons From a Decade of Use at a University Hospital

Abstract: After mupirocin use decreased, the ileS-2 encoding plasmid persisted in only a few Brazilian clone isolates. Our data on mupirocin-resistant MRSA incidence and mupirocin use strongly suggested that restricted use was related to decreased rates of mupirocin resistance at our hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 35 publications
(29 reference statements)
0
29
0
1
Order By: Relevance
“…S. aureus isolates were typed by PFGE after SmaI digestion as previously described (30). Banding patterns were analyzed by visual inspection and by computer-assisted analysis with GelCompar II (version 1.5) software (Applied Maths, Kortrijk, Belgium) using 0.40% optimization and 1% position tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…S. aureus isolates were typed by PFGE after SmaI digestion as previously described (30). Banding patterns were analyzed by visual inspection and by computer-assisted analysis with GelCompar II (version 1.5) software (Applied Maths, Kortrijk, Belgium) using 0.40% optimization and 1% position tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of genetic relatedness and characterization of isolates using pulsed-field gel electrophoresis (PFGE) of genomic DNA digested with SmaI were carried out as previously described (20). Banding patterns were determined by visual inspection and by using Bionumerics software, version 6.0 (Applied Maths) using the Dice index and the unweighted-pair group method with arithmetic average.…”
mentioning
confidence: 99%
“…44 Multiple studies have reported the arrival (or development) and spread of mupirocinresistant strains in settings where mupirocin is in frequent use, 45,46 including multiple reports of resistant strains spreading in Brazilian hospitals. 47,48 Mupirocin has also rarely been associated with toxic epidermal necrolysis after topical intranasal application, so a decision to apply it with great frequency would have to take this risk into account. 49 One recent meta-analysis of studies reporting the results of therapy for eradication of MRSA reported much conflicting evidence and concluded, "There is insufficient evidence to support use of topical or systemic antimicrobial therapy for eradicating nasal or extranasal MRSA.…”
Section: Several Studies In This Issue Of Infection Control and Hospitalmentioning
confidence: 99%